Academic and socio-emotional outcomes of young people with special educational needs and the role of parental educational expectations - Georgiana Mihut; Selina MacCoy; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2020)
This paper examines socio-emotional and academic outcomes among 17-year-olds with different types of special educational needs and the role of parental educational expectations in shaping these outcomes, using data from Ireland's national longitudinal study of children. The analysis takes account of a diversity of student and family characteristics as well as the effect of reading ability and socio-emotional wellbeing at age 9. The results show that lower parental academic expectations are linked to lower secondary performance of young people with special educational needs, even after controlling for academic achievements at age 9. Alongside other family characteristics, parental educational expectations at age 9 have long-term associations with both the socio-emotional and academic development of young people, providing important evidence that a more inclusive approach for supporting students with additional needs and their parents is needed.
Keywords: 330; special educational needs; academic achievement; socio-emotional outcomes; Parental educational expectations; Growing Up in Ireland